Charlie and the great glass elevator: the further adventures of Charlie Bucket and Willy Wonka, chocolate-maker extraordinary - Dahl, Roald; Schindelman, Joseph (New York : Puffin Books, 1998)
Taking up where Charlie and the Chocolate Factory leaves off, Charlie, his family, and Mr. Wonka find themselves launched into space in the great glass elevator.
Grade 6
Keywords: Outer space -- Fiction; Science fiction; Humorous stories